Randomized Noninferiority Trial of Telephone vs In-Person Disclosure of Germline Cancer Genetic Test Results. (27th February 2018) - Bradbury, Angela R; Patrick-Miller, Linda J; Egleston, Brian L; Hall, Michael J; Domchek, Susan M; Daly, Mary B; Ganschow, Pamela; Grana, Generosa; Olopade, Olufunmilayo I; Fetzer, Dominique; Brandt, Amanda; Chambers, Rachelle; et al.
Abstract: Background: Germline genetic testing is standard practice in oncology. Outcomes of telephone disclosure of a wide range of cancer genetic test results, including multigene panel testing (MGPT) are unknown. Methods: Patients undergoing cancer genetic testing were recruited to a multicenter, randomized, noninferiority trial (NCT01736345) comparing telephone disclosure (TD) of genetic test results with usual care, in-person disclosure (IPD) after tiered-binned in-person pretest counseling. Primary noninferiority outcomes included change in knowledge, state anxiety, and general anxiety. Secondary outcomes included cancer-specific distress, depression, uncertainty, satisfaction, and screening and risk-reducing surgery intentions. To declare noninferiority, we calculated the 98.3% one-sided confidence interval of the standardized effect; t tests were used for secondary subgroup analyses. Only noninferiority tests were one-sided, others were two-sided. Results: A total of 1178 patients enrolled in the study. Two hundred eight (17.7%) participants declined random assignment due to a preference for in-person disclosure; 473 participants were randomly assigned to TD and 497 to IPD; 291 (30.0%) had MGPT. TD was noninferior to IPD for general and state anxiety and all secondary outcomes immediately postdisclosure. TD did not meet the noninferiority threshold for knowledge in the primary analysis, but it did meet the threshold in the multiple imputation analysis. In secondary analyses, there were no statistically significant differences between arms in screening and risk-reducing surgery intentions, and no statistically significant differences in outcomes by arm among those who had MGPT. In subgroup analyses, patients with a positive result had statistically significantly greater decreases in general anxiety with telephone disclosure (TD –0.37 vs IPD +0.87, P = .02). Conclusions: Even in the era of multigene panel testing, these data suggest that telephone disclosure of cancer genetic test results is as an alternative to in-person disclosure for interested patients after in-person pretest counseling with a genetic counselor.